2015
DOI: 10.1371/journal.pone.0126363
|View full text |Cite
|
Sign up to set email alerts
|

Replication Study in a Japanese Population to Evaluate the Association between 10 SNP Loci, Identified in European Genome-Wide Association Studies, and Type 2 Diabetes

Abstract: AimWe performed a replication study in a Japanese population to evaluate the association between type 2 diabetes and 7 susceptibility loci originally identified by European genome-wide association study (GWAS) in 2012: ZMIZ1, KLHDC5, TLE1, ANKRD55, CILP2, MC4R, and BCAR1. We also examined the association of 3 additional loci: CCND2 and GIPR, identified in sex-differentiated analyses, and LAMA1, which was shown to be associated with non-obese European type 2 diabetes.MethodsWe genotyped 6,972 Japanese participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 41 publications
(47 reference statements)
1
14
1
Order By: Relevance
“…However, in a population‐based prospective cohort study from northern Sweden, rs2191349 was associated with elevated IFG risk . In the present study we found that rs10842994 was associated with a reduced risk of IFG, but a study conducted in a Japanese population examined the association of rs10842994 near KLHDC5 with susceptibility to diabetes . These two SNPs need to be evaluated further in a larger sample of the Chinese or in different populations.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…However, in a population‐based prospective cohort study from northern Sweden, rs2191349 was associated with elevated IFG risk . In the present study we found that rs10842994 was associated with a reduced risk of IFG, but a study conducted in a Japanese population examined the association of rs10842994 near KLHDC5 with susceptibility to diabetes . These two SNPs need to be evaluated further in a larger sample of the Chinese or in different populations.…”
Section: Discussioncontrasting
confidence: 51%
“…60 In the present study we found that rs10842994 was associated with a reduced risk of IFG, but a study conducted in a Japanese population examined the association of rs10842994 near KLHDC5 with susceptibility to diabetes. 34 These two SNPs need to be evaluated further in a larger sample of the Chinese or in different populations. The direction of the effect of most SNPs in the present study was the same as reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ides; DM, diabetes mellitus; IR, insulin resistance; T2DM, type 2 diabetes mellitus; WGAS, whole genome association study; ANTIGAD, anti glutamic acid decarboxylase; WHO, World Health Organization BACKGROUND Type 2 diabetes (T2D) is more prevalent in Asians than in Europeans (Sakai et al, 2013). The highest incidences of T2D (about 80%) are seen in developing countries.…”
mentioning
confidence: 99%